Pelatihan Cara Register dan Submit Artikel Pada OJS bagi Mahasiswa Pendidikan Sejarah, FKIP-Unpatti - Far-Far, Gazali; Kubangun, Nur Aida; Pattiasina, Johan (Universitas Pattimura, 2023)
Requiring the publication of scientific papers as one of the graduation requirements for undergraduate programs is a challenge for students. So this training was carried out to provide students with an understanding of the steps in registering and submitting articles to OJS. The method used in this training is an introduction to the OJS system and training to submit scientific articles via OJS. Training to submit scientific articles through OJS apart from introducing the OJS system, the next stage of activity is training to submit scientific articles through OJS. The aim is to provide knowledge and skills for students in writing scientific articles and registering and submitting scientific articles through OJS. Apart from that, the service team carries out evaluations related to activities in the form of: Routine mentoring once every semester. This is done to check whether students can/have actually submitted scientific articles via OJS. Periodic review every three months twice during one semester. This is done to share knowledge and insight with students that in writing scientific articles there are still many levels that need to be understood.